Quality assessment of amazonian honey sold in free markets (Research, Society and Development, 2024)
The objective of this research was to evaluate the quality of thirteen honey samples sold in street markets in the cities in the State of Pará, through physical chemical analyzes (total acidity, ash content, humidity and pH) and adulteration (dye, Fiehe, Lugol and Lund). The analyzes were carried out according to official methodologies of the Adolfo Lutz Institute. Comparing the results obtained with Normative Instruction (IN) No 11/2000 of the Ministério da Agricultura, Pecuária e Abastecimento (MAPA), it was observed that 31% of the samples differed from the limits established by legislation for the acidity and humidity parameters. For ash content and dye test, all samples met the standard stipulated by IN MAPA. The Fiehe and Lugol tests indicated that 61.5% of the samples were considered adulterated and for Lund c.a 54%. Thus, this study demonstrated the importance of quality control of this type of food and the need for constant and effective supervision by the competent bodies regarding the production and sale of honey in open-air markets.